2005
DOI: 10.1142/s0219876205000661
|View full text |Cite
|
Sign up to set email alerts
|

A Linearly Conforming Point Interpolation Method (Lc-Pim) for 2d Solid Mechanics Problems

Abstract: A linearly conforming point interpolation method (LC-PIM) is developed for 2D solid problems. In this method, shape functions are generated using the polynomial basis functions and a scheme for the selection of local supporting nodes based on background cells is suggested, which can always ensure the moment matrix is invertible as long as there are no coincide nodes. Galerkin weak form is adopted for creating discretized system equations, and a nodal integration scheme with strain smoothing operation is used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
135
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 216 publications
(136 citation statements)
references
References 18 publications
0
135
0
1
Order By: Relevance
“…In the PIM and RPIM, the compatibility characteristic is not ensured so the field function approximated could be discontinuous when nodes enter or leave the moving support domain. Liu et al suggested a linearly conforming point interpolation method (RC-PIM) [20] with a simple scheme for local supporting node selection, and a linearly conforming radial point interpolation method (RC RPIM) [21] to overcome the singular moment matrix issue and ensure the compatibility of the displacement.…”
Section: Introductionmentioning
confidence: 99%
“…In the PIM and RPIM, the compatibility characteristic is not ensured so the field function approximated could be discontinuous when nodes enter or leave the moving support domain. Liu et al suggested a linearly conforming point interpolation method (RC-PIM) [20] with a simple scheme for local supporting node selection, and a linearly conforming radial point interpolation method (RC RPIM) [21] to overcome the singular moment matrix issue and ensure the compatibility of the displacement.…”
Section: Introductionmentioning
confidence: 99%
“…The second and third terms are calculated adopting an approach similar to that proposed in [1] for the calculation of the � matrix. The last term is calculated over the smoothing domains using the standard Gauss integration approach.…”
Section: Spatial and Temporal Discretisationsmentioning
confidence: 99%
“…A wide class of efficient smoothed point interpolation methods (SPIMs) have been recently developed [1,2] by incorporating strain smoothing operation [2] to point interpolation methods (PIMs). In SPIMs, instead of using a compatible strain field, a smoothed strain field is constructed through a smoothing operation performed over smoothing domains.…”
Section: Introductionmentioning
confidence: 99%
“…The gradient smoothing was also used in the well-known widely used finite volume method (FVM) [32], the so-called quasi-conforming elements [33], and for the discretization of differential operator based on nodes [34]. It has been applied to resolve the material instabilities [14] and spatial instability in nodal integrated meshfree methods [15], and recently obtaining upper bound solution in meshfree point interpolation methods [18,19].…”
Section: A W 2 Formulation: a Window Of Opportunitiesmentioning
confidence: 99%
“…Proven types of smoothing domains are the cell-based smoothing domains that have been used in the smoothed FEM (or SFEM) [6][7][8] and cell-based smoothed point interpolation method (CS-PIM) [28]; node-based as used in the NS-PIM [16][17][18][19][20] and NS-FEM [24]; edge-based as in ES-PIM [26] and ES-FEM [25]; face-based FS-FEM [27]; as well as partial smoothing used in the α FEM [31]. Fig.…”
Section: A W 2 Formulation: a Window Of Opportunitiesmentioning
confidence: 99%